2016
DOI: 10.5721/eujrs20164943
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of multifractal features as global characteristics of WorldView-2 panchromatic satellite images

Abstract: In this work we analyse fractal and multifractal characteristics for description and extraction of information from VHR satellite images. We propose the degree of multifractality as a global descriptor of satellite image content and investigate its usefulness for classification of WorldView-2 image chips into main land cover types. The research confirmed that it is possible to use the textural features as efficient global descriptors of WorldView-2 panchromatic image content. Results show that the degree of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 61 publications
(85 reference statements)
4
12
0
Order By: Relevance
“…In general, the method was effective in automatically assigning image subsets to certain classes. We also showed that the degree of multifractality can be a very effective descriptor of image content, compared to other textural features [47]. However, it should be noted that our global analysis was exclusively focused on a panchromatic band of satellite imagery.…”
Section: Multifractalsmentioning
confidence: 64%
See 4 more Smart Citations
“…In general, the method was effective in automatically assigning image subsets to certain classes. We also showed that the degree of multifractality can be a very effective descriptor of image content, compared to other textural features [47]. However, it should be noted that our global analysis was exclusively focused on a panchromatic band of satellite imagery.…”
Section: Multifractalsmentioning
confidence: 64%
“…, where ( , ) is the greyscale intensity at point ( , ), and is the set of all pixels in box . It is worth noting that in the context of multifractal analysis, different measures can be constructed that emphasise various effects and describe different physical processes in the considered data ( [47,53]). To facilitate the results' description, we divided the spectrum into six zones (VIS, NIR, A 1, SWIR 1, A 2 and SWIR 2).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations